"There's a big tag on my head": exploring barriers to treatment seeking with women who use methamphetamine in Sydney, Australia - Brendan Clifford; Kate Van Gordon; Fiona Magee; Victoria Malone; Krista J. Siefried; Duncan Graham; Nadine Ezard (BMC, 2023)
Abstract Background Australia has a high prevalence of regular use of methamphetamine. While half of people who use methamphetamine regularly are women, they make up only one third of people seeking treatment for methamphetamine use disorder. There is a lack of qualitative research into the facilitators and barriers to treatment for women who use methamphetamine regularly. The study seeks a better understanding of the experiences and treatment preferences of women who use methamphetamine, to inform person-centred changes in practice and policy that break down barriers to treatment. Methods We conducted semi-structured interviews with 11 women who frequently use methamphetamine (at least once a week), and who are not engaged in treatment. Women were recruited from health services surrounding a stimulant treatment centre at an inner-city hospital. Participants were asked about their methapmhetamine use and health service needs and preferences. Thematic analysis was completed using Nvivo® software. Results Three themes were developed from participants' responses around experiences of regular methamphetamine use and treatment needs: 1. Resistance of stigmatised identity including dependence; 2. Interpersonal violence; 3. Institutionalised stigma. A fourth set of themes on service delivery preferences were also elicited, including continuity of care, integrated health care, and provision of non-judgmental services. Conclusion Gender-inclusive health care services for people who use methamphetamine should actively work to address stigma, support a relational approach to assessment and treatment, and seek to provide structurally competent health care that is trauma and violence informed, and integrated with other services. Findings may also have application for substance use disorders other than methamphetamine.